METODA BEDA HINGGA PADA PERSAMAAN KDV GELOMBANG INTERFACE - Wiryanto, L.H; Djohan, Warsoma (MATEMATIKA, 2006)
Propagation of interfacial wave, modeled in an equation of KdV type, is solved numerically. A finite different method is used to construct a system of linear equations from the model, and the system is solved by Gauss-Seidel method. This numerical procedure is firstly tested for solitary wave, which gives agreement to the analytical solution, and is then used to observe a simulation of wave propagation generated on the left by a generator, for some various values of parameters, depth and fluid density